2020
DOI: 10.1186/s12935-020-01656-3
|View full text |Cite
|
Sign up to set email alerts
|

FABP7 is a potential biomarker to predict response to neoadjuvant chemotherapy for breast cancer

Abstract: Background Early prediction of response to neoadjuvant chemotherapy (NAC) is critical in choosing appropriate chemotherapeutic regimen for patients with locally advanced breast cancer. Herein, we sought to identify potential biomarkers to predict the response to neoadjuvant chemotherapy for breast cancer patients. Methods Three genomic profiles acquired by microarray analysis from subjects with or without residual tumors after NAC downloaded from the GEO database were used to screen the differentially express… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A high level of fatty acid binding protein 7 (FABP7) is correlated with poor prognosis in several types of malignant tumors (43). A recent study demonstrated that FABP7 was a favorable biomarker for predicting better response to neoadjuvant chemotherapy (NAC) in breast cancer patients (44). Immune cell infiltration is a key factor affecting tumor progression and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…A high level of fatty acid binding protein 7 (FABP7) is correlated with poor prognosis in several types of malignant tumors (43). A recent study demonstrated that FABP7 was a favorable biomarker for predicting better response to neoadjuvant chemotherapy (NAC) in breast cancer patients (44). Immune cell infiltration is a key factor affecting tumor progression and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…FABP7 is expressed in many types of tumors, including brain, breast, colorectal, and prostate cancers, and is likely to play important roles in various cancers. FABP7 has been associated with response to chemotherapy and may be a potential biomarker predicting responses of breast cancer to neoadjuvant chemotherapy [32]. In addition, increased levels of FABP7 have been associated with reduced 14 Disease Markers survival and a higher incidence of brain metastases in patients with HER2+ breast cancer [10].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, the data was provided by public databases without cost, which led to the development of high-throughput sequencing at a high rate of speed, by mingling TCGA, GEO, GTEx, CCLE and other databases [28][29][30][31][32]. High-throughput genomic studies provided cutting-edge sights into the molecular mechanisms and identi ed new potential targets of breast cancer [33][34][35][36]. Nevertheless, using a single biomarker for predicting often relatively lower predictive effects, and a risk model for predicting the OS and DRFS of patients [37][38][39][40][41][42][43] and a nomogram were popular which showed superior predictive effects as a better alternative [18, [44][45][46].…”
Section: Discussionmentioning
confidence: 99%